2016
DOI: 10.1016/j.srhc.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Emotional, physical, and sexual abuse and the association with symptoms of depression and posttraumatic stress in a multi-ethnic pregnant population in southern Sweden

Abstract: Results Of 1003 women, 78.6% were native and 21.4% were non-native Swedish-speakers.Native and non-native Swedish-speakers experienced a similar proportion of lifetime abuse.Moderate emotional and physical abuse in childhood was significantly more common among non-native Swedish-speakers. While sexual abuse in adulthood was significantly more prevalent among native Swedish-speakers. Emotional and sexual abuse were significantly associated with symptoms of depression for both natives and non-natives. Physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
2
6
1
Order By: Relevance
“…Moreover, it was found that n=46 (11.22%), had history of trauma and n=27 (6.59%) were found depressed, and 79.27% individuals were depressed due to other risk factors, and thus proved that childhood abuse; neglect or loss in early life drastically increases the risk of developing depression. 26 According to previous researches, relationship was found between food and depression, as was observed in our research. n=193 (47.07 %) of adult population were taking healthy diet.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, it was found that n=46 (11.22%), had history of trauma and n=27 (6.59%) were found depressed, and 79.27% individuals were depressed due to other risk factors, and thus proved that childhood abuse; neglect or loss in early life drastically increases the risk of developing depression. 26 According to previous researches, relationship was found between food and depression, as was observed in our research. n=193 (47.07 %) of adult population were taking healthy diet.…”
Section: Discussionsupporting
confidence: 76%
“…Evidence of the potentially mediating role of depression in the CSA and parenting stress relationship is supportive of past research which indicates that people who experience CSA are vulnerable to developing depression (Wangel et al 2016) and that the experience of depression is associated with increased parental stress (Zajicek-Farber et al 2012). CSA may increase the risk of experiencing depression, which then affects the experience of parenting, or in turn CSA may cause difficulties in parenting which then may give rise to feelings of depression.…”
Section: Discussionsupporting
confidence: 52%
“…IPV prevalence varies in different studies conducted around the world, partly due to differences in definition, context and violence measurement methods (James et al, 2013;Sørbø et al, 2013;Wangel et al, 2016). According to the recent WHO reports, about 35% of women are with a mosaic of different ethnicities and cultures.…”
Section: Introductionmentioning
confidence: 99%